Small claims court's procedure for small claims business dispute - Kamarudin, Abdul Rani (Institute of Approved Company Secretaries, 2006)
Often than not, a person with a cause of action involving a small amount probably finds it even costly to pursue his or her cause of action than abandoning such cause of action. The cost involving in bringing the case to court, the involving court's papers which to a layman are difficult to draft and prepare, and further, the need to have an advocate and solicitor would accumulatively mean that it is not worth the trouble to pursue the matter since it has become 'too costly'. It is best and cheaper to simply rely on diplomacy, patient and luck in getting the money due and owing from the scrupulous guy. Though, justice that is delayed is as good as justice is being denied, but in this case, justice is not simply delayed, instead, is not seen to be done. The purpose of procedural law has always been to serve the ends of justice rather than to defeat a person's substantive rights based on technicalities unless the omission in the procedures are those that are so fundamental as to cause a miscarriage of justice. Thus, this paper attempts to look at how a plaintiff can pursue his cause of action in court where the amount is small at costs, making it worth the trouble to take the matter to court against the defendant. Accordingly, it will discuss the procedures involve when making such a claim in the light of the Malaysian Subordinate Court Rules 1980.